ESP: A Needs Analysis of Maritime English at Polimarin - Herdawan, Deri; Nindita, Kirtyana; Setyoningrum, Ari Ani Dyah (English Education: Jurnal Tadris Bahasa Inggris, 2021)
As an archipelagic country, Indonesia has long been known for its marine potential. This potential comes with new challenges, one of them being language problem. In this regard, English shows its prominent role as the international language to bridge communications. This research provided a needs analysis to identify the “necessities”, “lacks”, and “wants” in relation with English usage in maritime sector, specifically for those conducting internship at international ships. A qualitative approach and a descriptive design were applied in this research. The respondents consisted of 19 students of Polimarin who had completed internship at international ships, selected through total sampling technique. Their responses were collected by a questionnaire, complemented by interview. The collected data were then processed through a model consisting of four stages; data collection, data reduction, data display, and conclusion drawing. The “necessities” analysis revealed speaking and vocabulary as the most needed language skill and component. The “lacks” analysis showed that the syllabus used pays attention to English language skills and components evenly and that some respondents were underprepared before doing internship. The “wants” analysis came up with the simple present tense and the simple past tense as the most wanted tenses to master, pronouns as the most wanted grammatical feature and passive voice as the least wanted, all language functions evenly wanted, and group discussion as the most preferred learning activity. In conclusion, syllabus revision is due to improve the quality of English learning by accommodating the students’ “necessities”, “lacks”, and “wants”. Key words:ESP, Maritime English, Needs Analysis